A comparative approach to investigate heavy metals pollution in water and sediment of rivers (case study: Shahrud river) - Masoud Motamedi; Azita Behbahaninia; Forugh Farsad (علوم محیطی)
Introduction: One of the major contaminants of surface water resources are heavy metals. Heavy metals are natural components of the earth's crust, but human activities, and geochemistry and biochemical cycles may disturb their balance and release them into the environment. Release of pollutants into the aquatic environment will affect both water body and sediments, mostly sediments because they are less dynamic. Therefore, the concentration of heavy metals in river bed sediments reveals the pollution more intensity or its history far better than the water body. This research was carried out to determine the concentration of heavy metals in water and sediments of Shahrud River with the aim of determining the condition of heavy metal contamination and their sources in the study area. Material and methods: The Shahrud River is one of the main branches of the Sefid-Rud River which originates from the central Alborz Mountains, and is the only river in the southern part of the Alborz, which flows into the Caspian Sea. In this study, the concentration of heavy metals namely lead, cadmium, and arsenic in the Shahrud River and sediments in Lowshan city has been studied. Accordingly, the physiochemical properties of water and sediments were investigated in the first stage of sampling. Moreover, five sampling stations were determined and four sampling stages (autumn and winter 1395- spring and summer 1396) were carried out. Totally, 40 samples of water and sediments were taken along the river and the concentration of the considered parameters was measured. Results and discussion: The results demonstrated that COD was lower that the EPA standard in all sampling stations except station 5. Furthermore, regarding the IRWQI (SC) water quality index, all stations were ranked from average to bad classes of quality. The BOD in all sampling stations was higher than the EPA standard and according to the IRWQI (SC) index, all stations were ranked "semi-bad" to "bad" class of quality. The concentrations of lead, cadmium, and arsenic in water samples were compared with the guidelines of the Iranian National Standards Organization, Department of Environment, WHO and EPA. Moreover, it was ranked based on IRWQI (ST). Our results proved that the mean concentration of lead at all stations was lower than the standard except stations 3 and 4. The concentration of these heavy metals was relatively ranked into moderate to good classes. The average concentration of cadmium was lower than the standard at all stations except stations 1 and 3, and in regard to the descriptive index, it is categorized into good to fairly bad, respectively. In addition, the average concentration of arsenic was lower than the standard values at all stations. Also, it was classified as good, regarding the descriptive index. The concentration of heavy metals in sediment samples at sampling stations showed that the concentration of lead at all stations was lower than TEL values in NOAA and SQGs standards, and the concentration of cadmium at all stations was higher than the PEL values. The concentration of arsenic at all sampling stations was lower than the PEL values and at stations 2 and 5 was higher than TEL values. To quantitatively assess the sediments, contamination factors (Cf), degree of contamination (mCd), molar accumulation index (Igeo) and ecological risk assessment (Ri) were considered. Results showed high manmade contamination of cadmium and significant ecological risk in sediments of the study area. The use of phosphorus fertilizers in fields and gardens as well as the location of the cement factory, which is near the river, are the main causes of cadmium pollution in the study area. Additionally, the high levels of BOD and COD in water indicated high levels of organic contaminants, due to industrial and traditional olive processing centers, olive oil mills and poultry slaughterhouses in the study area. Conclusion: The study area was contaminated with heavy metals, which is mainly caused by the high concentration of cadmium in sediments of Shahrud River. It is essential to mention that its negative impact on humans, organisms and urban environment in Lowshan city and downstream of the Shahrud river is undeniable.